Pengaruh Metode Resitasi Terhadap Kemandirian Belajar Dan Kemampuan Pemecahan Masalah Pada Mata Pelajaran Matematika - Annisa Maryam Septiani; Eko Fajar Suryaningrat; Ejen Jenal Mutaqin (Institut Pendidikan Indonesia, 2023)
Education in Indonesia is in an emergency position, the cause of the low quality of education in Indonesia comes from internal and external factors. One of the internal factors includes learning independence and student intelligence in the form of problem solving abilities. This encourages researchers to determine the effect of the recitation method on learning independence and problem solving abilities in mathematics subjects for fifth grade students at SDN 02 Padasuka. This study uses a quantitative approach with experimental methods. Based on the results of the study, it was concluded that the Manova test for learning independence and problem solving abilities showed that the value of sig < 0.05 was 0.000 < 0.05. So that it can be stated that Ha is accepted, namely